Analysis of compounds possessing inhibitory properties on mice locomotor activity from essential oils of Ki Lemo bark (Litsea cubeba lour. Pers) - Muchtaridi .; Anton Apriyantono; Anas Subarnas; Slamet Budijanto (Indonesian Journal of Pharmacy, 2005)
Ki lemo barks has been used as traditional spasmolitic (called oils of massage) since a long time by ethnic of Dayak. The odors inhaled is presumed possessing inhibitory on mice locomotor activity. The present research has been done to determine the components in blood plasma of mice after inhalation of essential oil of ki lemo barks, and the possibility of their role in the inhibition on mice locomotor activity.Inhalation of essential oil of ki lemo bark (Litsea cubeba Lour. Pers) at the doses of 0.5 ml inhibit locomotor up to 60,75 %, whereas at the doses of 0.1 ml and 0.3 ml inhibit locomotor activity of 57,44 % and 54,20 %, respectively.Identification and quantification of volatile active compounds in the blood plasma were carried out by GC-MS analysis after half an hour, one hour, and two hours inhalation. The blood plasma of three mice were collected in heparin tube, isolated and concentrated by the C-18 column (100 mg-Seppak Waters) eluted with methanol and bidistilled water (60:40). The major compounds identified were citronellol, citronellal, α-terpineol, and 1,8-cineole. The blood level of those substances was increasing for one hour after inhalation but decreasing after two hours.Key words : essential oil of ki lemo bark (Litsea cubeba Lour. Pers), inhalation, locomotors.